The sharpshooter genus Aguana: taxonomic notes, two new species from Brazil, the female of A. imbricata, and updated key (Hemiptera: Cicadellidae: Cicadellini) - Mejdalani, Gabriel; Domahovski, Alexandre C.; Cavichioli, Rodney R. (Zootaxa, 2019)
The genus Aguana Melichar, 1926 previously included only two species from the Atlantic Forest of Southeastern Brazil. Here we provide a revised diagnosis for the genus and describe two new Brazilian species and the female of A. imbricata (Signoret, 1854). The new taxa are A. picinguaba sp. nov. (states of Rio de Janeiro, São Paulo, and Santa Catarina) and A. spitzi sp. nov. (State of São Paulo). Aguana species are very similar to one another externally and can be distinguished mainly by features of the male terminalia (especially of the aedeagus) and female sternite VII. A key to males and females of the genus is added (except the female of A. russata Young, 1977).